PELATIHAN PENGENALAN INVESTASI SAHAM PADA WARGA KELURAHAN PLAMONGANSARI, KECAMATAN PEDURUNGAN KOTA SEMARANG SEBAGAI ALTERNATIF PASSIVE INCOME - Patricia Dhiana Paramita; Cicik Harini (Universitas Pandanaran, 2022)
Passive income is an income that continues to grow when you are no longer doing business, such as quitting your job, or when your investment capital has returned. If passive income is managed properly, it will be able to become another source of income besides active income every month that is obtained from working or doing other productive businesses. Starting from the desire to invite residents to optimize passive income, the Pandanaran University Community Service team took the initiative to hold training on the introduction of stock investment as an alternative to passive income.So far,based on the observations of the residents of Plamongansari Village, active income has been prioritized and put aside passive income, even though investing in shares will bring benefits that can have a positive impact on improving people's living standards. Socialization about passive income with stock investment has never been done in Plamongansari Village. This is motivated by the absence of competent people in the field of stock investment who provide introduction and training to the residents of Plamongansari Village, which aims to increase the residents' passive income, thus requiring a continuous socialization, training and mentoring program regarding stock investment.Through a program of socialization, training and mentoring on stock investment and capital markets for residents, it is expected that citizens will change their mindside to manage passive income by investing in stocks. There is a need for cooperation with relevant agencie to provide socialization,counseling and assistance to residents of Plamongansari Village,such as from IDX (Indonesia Stock Exchange), securities companies and OJK (Financial Services Authority) in terms of providing regular and continuous training on how to do profitable and minimal risk stock investment and how to trade on the national stock exchange market. Keywords: passive income, stock investment